Polymer Brush Films with Varied Grafting and Cross-Linking Density via SI-ATRP : Analysis of the Mechanical Properties by AFM - Lilge, Inga (Springer Fachmedien Wiesbaden : Imprint: Springer Spektrum, 2017)
In her research, Inga Lilge focuses on a systematic study of poly(acrylamide) (PAAm) brushes prepared by surface-initiated atom transfer radical polymerization (SI-ATRP). In addition to the analysis of the time dependence of the polymer brush growth, the conformation of the polymer brushes is varied by grafting or cross-linking density. The results have practical implications for the study of cellular interactions on PAAm brushes since cell-substrate interactions are known to influence various cell characteristics, such as migration and adhesion. Contents Introduction to Polymer Brushes Preparation of Cross-Linked Polymer Brushes Utilization of Binary Monolayers for the Polymer Brush Synthesis Characterization of Modified Gold Surfaces AFM Nanoindentation in Water/Analysis of the Young's Modulus Target Groups Lecturers, students and researchers in chemistry, polymer chemistry, surface and materials science Chemists, surface and materials scientists The Author Inga Lilge finished her PhD at the University of Siegen, Department of Chemistry & Biology, Germany.
Keywords: Chemistry.; Physical chemistry.; Nanochemistry.; Nanotechnology.; elektronické knihy; electronic books